2018
DOI: 10.1155/2018/6317434
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Protective Effects of Morinda citrifolia Leaf Extract on Postmenopausal Rats Fed with Thermoxidized Palm Oil Diet: Evidence at Microscopic Level

Abstract: Atherosclerosis is now well understood as an inflammatory disease instead of lipid storage disorder; however, the conventional treatment is not targeted on treating the inflammation. Morinda citrifolia L. (Rubiaceae) leaf or noni leaf, which is a medicinal food (ulam) used in Traditional Malay Medicine to prevent chronic diseases, may have the potential to be formulated into a functional antiatherosclerotic agent. This study aimed to investigate the effectiveness of Morinda citrifolia leaf extract (MCLE) treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Furthermore, previous studies attributed the vascular dysfunction to the increased lipid concentration besides the initiation of inflammatory processes [ 56 , 60 ]. The reported accumulated blood cells and perivascular adipose tissue deposition indicated the presence of active inflammation as clarified by previous study [ 61 ].…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, previous studies attributed the vascular dysfunction to the increased lipid concentration besides the initiation of inflammatory processes [ 56 , 60 ]. The reported accumulated blood cells and perivascular adipose tissue deposition indicated the presence of active inflammation as clarified by previous study [ 61 ].…”
Section: Discussionmentioning
confidence: 56%
“…Rare phytoactive substances with health promoting potential isolated from the leaf includes dehydromethoxygaertheroside, dehydroepoxymethoxygaertheroside, borreiagenin [14], citrifoside, pheophorbide A, pyropheophorbide A, ursolic acid [15], and flavanoids [16]. Previously, we have reported that MC leaf extract possesses antiatherosclerotic effect through its anti-inflammatory activity in the aorta [17]. Since the liver is an indicator of vascular health by secreting and regulating various molecular cardiovascular disease (CVD) risk factors, we further investigated the mechanism of action of MC leaf by looking into the detailed histological and ultrastructural changes in the liver [18].…”
Section: Introductionmentioning
confidence: 99%
“…As an anti-cancer compound, Nordamnacanthal (NDAM) has links with NK cells, T-helper, and cytokines in the body [27]. In addition, the incidence of atherosclerosis associated with TNF-and IL-1B cytokines can also be lowered and affect blood lipid profiles [28].…”
Section: Results the Anatomy Liver Of Ratsmentioning
confidence: 99%